Standardised CPUE of cod and hydrographic data - Bartolino, Valerio; Tian, Huidong; Bergström, Ulf; Jounela, Pekka; Aro, Eero; Dieterich, Christian; Meier, H.E. Markus; Cardinale, Massimiliano; Bland, Barbara; Casini, Michele (Dryad Digital Repository, 2017)
The dataset contains information on all the variables at the aggregation level of individual bottom trawl hauls as used in the analyses presented in "Spatio-temporal dynamics of a fish predator: density-dependent and hydrographic effects on Baltic Sea cod population". Year: year when the cod sample was collected; Lon: longitude (decimal-degree) of the position where the cod sample was collected; Lat: latitude (decimal-degree) of the position where the cod sample was collected; Depth: bottom depth (m) where the cod sample was collected; AG3: catch-per-unit-effort (kg/h) of cod of age 3+ of the trawl station; Oxy: modelled bottom oxygen (ml/L) associated to the trawl station; Sal: modelled bottom salinity (psu) associated to the trawl station; Crv: cod reproductive volume (km3) estimated for the year and ICES subdivision of the trawl station; Stk: stock size (thousands) of the eastern Baltic cod in the year of the sample from stock assessment (ICES 2013).